1994
DOI: 10.1364/ol.19.002137
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical and noise properties of laser diodes subject to strong optical feedback

Abstract: Dynamical and noise properties of laser diodes subject to strong optical feedback have been investigated. Under strong optical feedback a conventional rate-equation approach is not valid, and thus an iterative traveling-wave model has been developed to describe this operating regime. Attention has been given to identifying the transition from stable strong-feedback operation to the coherence collapse regime obtained with moderate optical feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…The phase in the function is obviously given by (30) where is an integer. Equation (27) is applicable for an arbitrary amount of OFB. The so-called Lang and Kobayashi model [15] is obtained from (27) by supposing weak OFB with and a constant phase due to the round trip of time delay , such that we get for…”
Section: Modified Rate Equationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The phase in the function is obviously given by (30) where is an integer. Equation (27) is applicable for an arbitrary amount of OFB. The so-called Lang and Kobayashi model [15] is obtained from (27) by supposing weak OFB with and a constant phase due to the round trip of time delay , such that we get for…”
Section: Modified Rate Equationsmentioning
confidence: 99%
“…When more than 20, the laser shows CW operation and pulsing operation with again. In such calculations, the round trips between the front facet and external mirror were limited to a single round trip , which is effective for the case of small reflectivity at the front facet (e.g., AR-coated facet) [26], [27]. Nevertheless, we compare the results in Fig.…”
Section: A Variation Of the Laser Operation With Ofbmentioning
confidence: 99%
See 2 more Smart Citations
“…Optical feedback also influences the noise properties of semiconductor lasers, [8][9][10][11][12][13][14][15][16][17][18]. Petermann [15] has both theoretically and experimentally demonstrated that the relative intensity noise (RIN) increases rapidly in regime IV.…”
Section: Introductionmentioning
confidence: 99%